The CYCLOPS Response Element in the NIN Promoter Is Important but Not Essential for Infection Thread Formation During Lotus japonicus–Rhizobia Symbiosis - Akira Akamatsu; Miwa Nagae; Naoya Takeda (Molecular Plant-Microbe Interactions, 2022)
The establishment of the legume-rhizobia symbiosis, termed the root-nodule symbiosis (RNS), requires elaborate interactions at the molecular level. The host plant–derived transcription factor NODULE INCEPTION (NIN) is known to be crucial for RNS, regulating associated processes such as alteration of root hair morphology, infection thread formation, and cell division during nodulation. This emphasizes the importance of the precise spatiotemporal regulation of NIN expression for the establishment of RNS; however, the detailed role of NIN promoter sequences in this process remains unclear. The daphne mutant, a nin mutant allele containing a chromosomal translocation approximately 7 kb upstream of the start codon, does not form nodules but does form infection threads, indicating that the region within 7 kb of the NIN start codon contributes to NIN expression during infection thread formation. CYCLOPS binds to a CYCLOPS response element (CYC-RE) in the NIN promoter, and cyclops mutants are defective in infection thread formation. Here, we performed complementation analysis in nin mutants, using various truncated forms of the NIN promoter, and found that the CYC-RE is important for infection thread formation. Additionally, the CYC-RE deletion mutant, generated through CRISPR/Cas9 technology, displayed a significant reduction in infection thread formation, indicating that the CYC-RE is important for the fine-tuning of NIN expression during this process. However, the fact that infection thread formation is not completely abolished in the CYC-RE deletion mutant suggests that cis and trans factors other than CYCLOPS and the CYC-RE may cooperatively regulate NIN expression for the induction of infection thread formation. [Graphic: see text] Copyright © 2022 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.